Antioxidant effect of Lactobacillus fermentum HFY02-fermented soy milk on D-galactose-induced aging mouse model - Tiantian Hu; Rui Chen; Yu Qian; Ke Ye; Xingyao Long; Kun-Young Park; Xin Zhao (Food Science and Human Wellness)
This study aimed to investigate the antioxidant effect of soybean milk fermented by a new type of Lactobacillus fermentum (LF-HFY02) by using D-galactose induced aging mice model. Firstly, the optimal fermentation conditions was screened out by detecting the effects of different fermentation temperature and time on the active components and antioxidant activity of soybean milk in vitro. And then unfermented soybean milk and the soybean milk fermented by different Lactobacillus was given by gavage to D-galactose-induced aging mouse. The activities of GSH, GSH-Px, SOD, CAT and T-AOC in serum, brain and liver of soybean milk fermented by LF-HFY02 were significantly increased, while the content of MDA and the level of AGEs in hippocampal were significantly decreased compared with D-galactose induced group. Further more, the mRNA expression of GSH and SOD in mouse liver were obviously up-regulated by soybean milk fermented by LF-HFY02. The skin tissue structure of mice in the LF-HFY02 fermented soybean milk group was more complete, the collagen fibers were increased and arranged orderly and liver inflammation has improved compared with the model group. And Western blot analysis showed that LF-HFY02 effectively upregulated EGFR, SOD and GSH protein expression in mouse liver. These findings suggest that LF-HFY02 can effectively prevent D-galactose-induced oxidation and aging in mice, and the effect was even better than that of the Lactobacillus delbruechii subsp. bulgaricus and vitamin C. Thus, LF-HFY02 may be potentially employed as a probiotic strain. In conclusion, soybean milk fermented by LF-HFY02 can increase the content of antioxidant factors and the activity of antioxidant enzymes by regulating gene and protein expression, and finally inhibit the process of tissue cell peroxidation, and improve the oxidative damage of mouse skin and liver. The results could provide a basis for the research and development and industrial production of probiotic-related fermented soybean milk products.